KEMAMPUAN LITERASI INFORMASI MAHASISWA PROGRAM STUDI TADRIS MATEMATIKA ANGKATAN 2021 UIN MAULANA MALIK IBRAHIM MALANG DALAM PENYELESAIAN TUGAS MAKALAH BERDASARKAN MODEL SEVEN PILLARS - Budi, Fayza Naila Alam; Putri, Ega Anasya (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2023)
This study focuses on students’ information literacy skills in completing academic papers. The level of the informants’ abilities has not been comprehensively and in-depth explored, making it necessary to conduct this research. This study employs a descriptive qualitative approach, aiming to obtain a clear understanding of the informants’ information literacy competencies in preparing paper assignments. The conceptual framework for assessing information literacy skills uses the SCONUL Seven Pillars Information Literacy Research Lens. The informants consist of five students from the Mathematics Education (Tadris) program, class of 2021, at UIN Maulana Malik Ibrahim Malang. The results indicate that the informants have not fully mastered information literacy skills. The first informant has not mastered the competencies of managing, gathering, and evaluating information. The second informant has not mastered planning, gathering, evaluating, and managing competencies. The third informant has not mastered scoping, gathering, managing, and evaluating competencies. The fourth informant has not mastered scoping, planning, gathering, and managing competencies. The fifth informant has not mastered scoping, evaluating, and managing competencies. Factors inhibiting the development of information literacy skills include limited participation in completing paper assignments, insufficient availability of library collections, ineffective use of keywords that match information needs which increases search time, and the lack of citation use in paper preparation.